“Diseño e implementación de un sistema autónomo para el desarrollo cognitivo para niños de 2 a 3 años ” - Guevara Cruz, Ronny Stalin (2018)
The cognitive field is an essential aspect of the development of the child from two to three years, the child is consolidating the language, begins to understand abstract concepts and relate some concepts with others, improves their attention span, memory and progresses in knowledge and control of his/her own body. Technologies affect the development of children, either positively or negatively, but the use of these new technologies must be a learning experience. Therefore, in this research project it is intended to design and implement an autonomous system for cognitive development in children from 2 to 3 years, allowing a direct interaction with the computer, providing the child with various activities that influence their cognitive development in a positive way. One of the first tasks in the present project was to review the contributions of the different psychological theories of cognitive nature by Pozo, Bruner, Vygotski and Jean Piaget; without leaving aside the investigation of the different cognitive skills developed by children ages 2 to 3 years. To achieve this goal, it was decided to design a graphical GUIDE interface for Matlab in its ®17 version, within it algorithms for digital image processing and speech recognition were implemented, fundamental pillars for the development of each of the activities within the interface, which will improve the cognitive abilities of children put to the test. Based on this, the different resources necessary for the development of each activity were designed, simulated and constructed, such as the TET (Early Stimulation Cards), the interactive keyboard and the reading box. Finally, the tests of the autonomous system for cognitive development were carried out in a group of children ages 2 to 3 years old from the city of Riobamba. Significant results were obtained when using the proposed system.